The political economy of shopkeeping in Milan, 1886-1922 - Morris, Jonathan 1961- (Cambridge University Press, 1993)
From the mid–1880s a shopkeeper movement developed in Milan, centred around a shopkeeper newspaper, a federation of shopkeeper trade associations, and a shopkeeper bank. In 1904 shopkeeper representatives initiated a sequence of events that led to the fall of the first radical-socialist administration within the city. The author explains these events with reference to the business of shopkeeping itself. He analyses the trades, techniques, tax structure and topography of the Milanese retail sector, and traces the history of the contest between shops and cooperatives and the shopkeeper's changing relationship with his employees and with his clientele. The final chapter confronts the crucial question of why the Milanese shopkeepers were to be found on the political right in the years leading up to the Fascist takeover. This is the first book to deal with any aspect of the Italian petite bourgeoisie
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1886-1922; Geschichte; Politik; Retail trade / Government policy / Italy / Milan / History; Stores, Retail / Italy / Milan / History; Merchants / Italy / Milan / History; Einzelhandel; Italien; Milan (Italy) / Commercial policy / History; Milan (Italy) / Commerce / History; Mailand